2006
DOI: 10.1029/2006gl026733
|View full text |Cite
|
Sign up to set email alerts
|

Heat signature on the Chelungpu fault associated with the 1999 Chi‐Chi, Taiwan earthquake

Abstract: [1] We have made observations of a heat signature that is associated with the frictional heat generated at the time of faulting for a large earthquake. Temperature measurements in a borehole that intersects the Chelungpu fault at a depth of about 1100 m, show a small increase near the fault even six years after the earthquake. The temperature signature has a symmetric shape with a width of about 40 m and is centered on the fault that slipped about 5 m during the 1999 Chi-Chi, Taiwan earthquake. The small ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
154
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(165 citation statements)
references
References 15 publications
8
154
2
1
Order By: Relevance
“…Drilling has revealed that heat generated by > 50 m of slip during the Tohoku-Oki 2011 earthquake (moment magnitude M w = 9.0) produced only a small temperature anomaly, requiring an average friction coefficient during slip of < 0.1 (ref. 10); similar results were found after the Wenchuan 2008 and Chi-Chi 1999 earthquakes 11,12 . Plate boundary faults must, therefore, be composed of materials that are mechanically weak on long timescales, even if weakness is a transient phenomenon during movement.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Drilling has revealed that heat generated by > 50 m of slip during the Tohoku-Oki 2011 earthquake (moment magnitude M w = 9.0) produced only a small temperature anomaly, requiring an average friction coefficient during slip of < 0.1 (ref. 10); similar results were found after the Wenchuan 2008 and Chi-Chi 1999 earthquakes 11,12 . Plate boundary faults must, therefore, be composed of materials that are mechanically weak on long timescales, even if weakness is a transient phenomenon during movement.…”
supporting
confidence: 64%
“…Drilling studies have taken place in response to earthquakes of M w = 6.9-9.0 in Japan, Taiwan, China and the USA 8,[10][11][12][18][19][20][21] , and the results do not reveal anomalous temperatures or fluid pressures (Fig. 1).…”
mentioning
confidence: 94%
“…Studies of processes that may mask or dissipate the frictional heat signal have focused on steady state topographically driven or buoyancy-driven groundwater flow [Williams and Narisimhan, 1989;Saffer et al, 2003;Fulton et al, 2004] and the effects of heterogeneous thermal properties [Tanaka et al, 2007;Fulton and Saffer, 2009a]. One candidate for obscuring a frictionally generated thermal signal that has not been fully explored is transient groundwater flow following an earthquake [e.g., Kano et al, 2006;Scholz, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…This magnitude of friction is hypothesized to generate large thermal anomalies on natural faults with large slip rates and/or large total displacements, assuming hydrostatic pore pressure. Curiously, analysis of surface heat flow data [e.g., Brune et al, 1969;Lachenbruch and Sass, 1980;Wang et al, 1995] and subsurface temperature profiles [Yamano and Goto, 2001;Kano et al, 2006;Tanaka et al, 2006Tanaka et al, , 2007 that cross fault zones do not show substantial, unequivocal anomalies from frictional heating. These observations prompt two questions: (1) could the frictional resistance be as large as expected from Byerlee's law and hydrostatic pore pressure, but the heat signal is masked or dissipated by other processes?…”
Section: Introductionmentioning
confidence: 99%
“…Temperature profiles across the fault are the most direct way to quantify coseismic friction [e.g., Tanaka et al, 2006;Kano et al, 2006]. Because most frictional resistance is dissipated as heat, any temperature increase on the fault at the time of the earthquake is potentially interpretable as a cumulative measure of frictional heat generated during slip [Lachenbruch and Sass, 1980].…”
Section: Key Borehole Measurements: Temperature Stress and Strainmentioning
confidence: 99%